Influência da suplementação de retinol palmitato sobre os níveis de vitamina A no leite de puérperas saudáveis - Lourenço, Raquel Maria da Silva (2006)
The tendency towards reduction of serum retinol levels, an existing placental barrier and the increase of retinol demand, are factors that place puerperal and lactating women at risk for Vitamin A deficiency. This micronutrient is an essential component of vital processes such as differentiation, cellular proliferation, and apoptosis. The objective of this study is to evaluate the effect of palmitate retinol supplementation (100.000UI) upon the milk retinollevels in puerperal women at the Januário Cicco University Maternity Hospital. This intervention has been adopted by the Ministry of Health since 2002. The longitudinal experiment was conducted with 106 puerperal women (68 comprised the supplemented group and 38 the control group). The High Performance Liquid Chromatography (HPLC) method was used to dose the retinol of the milk and serum samples, and the creamtocrit method to determine the milk fat levels. The retinol means for the colostrums were 99.0 ± 64.4 ug/dL and 160.1 ± 94,4 ug/dl 6 hours afier supplementation; 68.9 ± 33.5 ug/dL for the transitional milk, and 30.6 ± 15.2 ug/dL for the mature milk of the supplemented group. Ali the difterences between means were statistically significant. The difterence between retinol means in the control group were also significant, with these being greater in the colostrum, 88.6 ± 62.1 ug/dL with 61.9 ± 30.1 ug/dl in the transition milk and 32.9 ±32.9 ± 17.6 ug/dL in the mature milk. No significant difference was observed in the retinol means of the three types ot milk in the supplemented group when compared to their respective means in the control group. The prevalence in serum (35.1 % and 81.1 % for the cutting point 20 ug/dL, respectively) and in milk (51.4%) revealed vitamin A deficiency as a public health problem. COlostrum, transition, and mature milk tats varied similarly in the supplemented group (1,92 ± 0,96; 3,25 ± 1,27 and 3,31 ± 1,36 grams) and in the control group (1,87 ± 1,14; 3,25 ± 1,31 and 3,36 ± 1,67 grams), with an observed difference between the colostrum/transition milk and the colostrum/mature milk fats. No difference was observed between the groups. The study showed that the 200.000UI supplementation was not sufficient to increase the milk retinol to the desired levels nor to meet the demands of the mothers with deprived hepatic reserves. It is suggested that another similar dose be offered within 30 days or less, and within 2 months post-partum, while continual/y monitoring for possible pregnancy